Families’ concerns about the care of children with technology-dependent special health care needs - de Souza Esteves, Joyce; Faria da Silva, Liliane; da Conceição, Daniele Santos; Dórea Paiva, Eny (Investigación y Educación en Enfermería, 2015)
Objective. To identify concerns of family members of Children with Special Health Care Needs (CSHCN) as far as care related to using technology, and to discuss nurses’ performance in the face of these concerns. Methodology. Qualitative descriptive research, developed through February and March 2014, through semi-structured interviews with six family members, caregivers of technology-dependent CSHCN who are followed at a University Hospital in Rio de Janeiro. The setting chosen was the family members’ home. Data were submitted to content analysis. Results. Concerns were distributed in a timeframe, divided between those occurring the moment the family members received the information about the technological device needed, then those which arose while accompanying the child during hospitalization, and finally those that remained after the hospital discharge. Conclusion. The family needs information and support from nurses, because different concerns emerge throughout the treatment and accompaniment of a technology-dependent child. How to cite this article: Esteves JS, Silva LF, Conceição DS, Paiva ED. Families’ concerns about the care of children with technology-dependent special health care needs. Invest Educ Enferm. 2015; 33(3):